Radiological signs supporting idiopathic intracranial hypertension in symptomatic patients with lumbar puncture opening pressure < 250 mm - Anat Horev; Tal Eliav; Inbal Sherer; Ron Biederko; Gal Ben-Arie; Ilan Shelef; Yair Zlotnik; Tamir Regev; Erez Tsumi; Asaf Honig; Gili Givaty (Scientific Reports, 2024)
Abstract Lumbar puncture opening pressure (LPOP) exceeding 250mmH2O is key in diagnosing idiopathic intracranial hypertension (IIH), per revised Friedman’s criteria. Some patients do not meet LPOP criteria (with or without papilledema), despite having IIH-related symptoms and neuroimaging findings. This study aimed to investigate the radiological findings and clinical symptoms in patients suspected of having IIH without meeting the LPOP criteria. We retrospectively evaluated cerebral venous sinus stenosis using the conduit Farb score (CFS) and other radiological findings suggestive of IIH by computed tomography venography and magnetic resonance venography in females ≥ 18 years-old with chronic headaches, suspected IIH, and LPOP < 250 mm. Eighty-eight women (56 with LPOP < 200 mm H2O and 32 with LPOP ranging between 200 and 250mmH2O) were included. Among patients with LPOP 200–250mmH2O, 40% (12) exhibited three or more radiological findings supporting IIH, compared to 17% (8) in the LPOP < 200 mmH2O group (p = 0.048). Cerebral venous stenosis (CFS ≤ 5) was observed in 80% (24) of those with LPOP 200–250 mmH2O, contrasting with 40% (19) of those with LPOP < 200 mmH2O (p < 0.001). Cerebral venous stenosis was significantly more common in patients with LPOP 200–250 mmH2O than < 200 mmH2O, suggesting that they may benefit from IIH treatment.